CHARACTERIZATION OF AQUIFER STRUCTURES IN THE NORTHEAST BASEMENT ROCK OF BURKINA FASO - Nakolendousse, Samuel; Bonogo, Christian; Kafando, Sayoba; Bembamba, Michel (International Journal of Research -GRANTHAALAYAH, 2023)
This characterization study of the aquifer horizons is based on the geostatistical analysis of the drilling data in order to map the intrinsic parameters of the aquifers, namely the size of the alterations and the size of the fissured fringe. The STRM data were also used to map the topographic levels. Cross-analysis of all these parameters with borehole flow rates allowed us to define a context pattern that is favorable to groundwater deposits, by identifying the influence of the size of these parameters on productivity. The application of the geophysical method (electric drag and geoelectric tomography) has made it possible to obtain a 2D vertical section of the subsoil structure based on the distribution of electrical resistivity. The alteration profile includes the alterite reservoir, the fissure reservoir located above the solid rock sometimes affected by fractures (fault). The size of these different horizons varies from one point to another, thus defining contexts that are more or less favorable for the existence of groundwater deposits. The alteration thickness (AT) mapping defined two map units: alteration thicknesses of 15m or less and those greater than 15m. Erosion would have played a large role in this distribution as there is a clear link between alteration thickness and topography. The alteration thickness (AT) unit of less than or equal to 15 m has great surface water potential. It is the area where the topography is fairly low, and the fractured edges are generally of considerable thickness. They frequently coincide with the large shallow areas drained by the major waterways.